Experimental evaluation of an innovative radial-flow high-temperature packed bed thermal energy storage. (1st April 2022) - Trevisan, Silvia; Wang, Wujun; Guedez, Rafael; Laumert, Björn
Graphical abstract: Highlights: A novel radial flow packed-bed thermal energy storage is presented. Experimental performance investigation conducted up to maximum temperature of 700 °C. Limited pressure drops and thermal losses are measured. A maximum thermal efficiency of about 72 % is measured. Non-uniform porosity is observed and design improvements are suggested. Abstract: High-temperature packed-bed thermal energy storage represents an economically viable large-scale energy storage solution for a future fossil-free energy scenario. The present work introduces first-of-a-kind experimental setup of a radial packed-bed TES, and its performance assessment based on experimental investigations. The storage performance is analyzed based on a set of dimensionless criteria and indicators. The laboratory-scale prototype has an energy capacity of 49.7 kWhth and working temperatures between 25 °C and 700 °C with a non-pressurized dry airflow. The influence of different working fluid mass flow rates and inlet temperatures during charge and discharge is assessed. The proposed storage design ensures limited pressure drop, lower than 1 mbar, and thermal losses, about 1.11 % during dwell after charging at 700 °C until a state of charge of 55.8 %. A maximum overall thermal efficiency of 71.8 % has been recorded and trade-offs between efficiency, thermal uniformity, and thermocline thickness are highlighted. This work testifies that reduced pressure drops are the key advantage of radial-flow packed-bed designs. Thermocline degradation is shown to be the main weak point of this thermal energy storage design.